Modification and optimization strategies for turbine arbitrary blade tips. (September 2019) - Jin, Jiahui; Song, Yanping; Yu, Jianyang; Chen, Fu
The influence of different arbitrary blade tip shapes on restraining the tip leakage flow in a highly loaded turbine cascade has been numerically studied. A combined method of establishing and optimizing the arbitrary blade tip shape is proposed by using B-spline surface modeling, Kriging model and genetic optimization algorithm. The results show that the Kriging model established by the B-spline surface modeling method can accurately fit the relationship between the arbitrary blade tip shape and the relevant aerodynamic parameters. The optimal leakage mass flow tip and the optimal total pressure loss tip obtained by genetic algorithm both have strong inhibitory effects on tip leakage flow. Compare to the flat tip at 1%H gap height, the tip leakage mass flow of the optimal leakage mass flow case and the optimal total pressure loss case decrease by 11.14% and 10.23%, respectively, the area-average total pressure loss at exit section is reduced by 8.08% and 7.41%, respectively.